The United States’ decision to reduce its contribution to UN Peacekeeping operations: A neorealist perspective - Abdullah Akbar Rafsanjani; Bobyano Dolyamano Blessing Purba (Priviet Social Sciences Journal, 2026)
The reduction in the United States' contribution to the United Nations, particularly in peacekeeping operations, has implications for mission operational capacity and global security stability. For decades, UN funding has played an important role in maintaining security and supporting reconciliation, the restoration of state institutions, and the protection of civil society in post-conflict regions. The United States, as the largest contributor, with a contribution of 26.95% to the UN peacekeeping budget by 2025, is one of the main pillars of mission sustainability through financial and logistical support. However, during Donald Trump’s second term, America First policies encouraged reduced contributions to various multilateral mechanisms, including peacekeeping operations in the Middle East. This study uses a qualitative approach with a case study design and Kenneth Waltz and John Mearsheimer’s offensive realism framework to analyze the factors behind the policy and its implications for UN peacekeeping operations. The results show that funding cuts are influenced by a combination of domestic political dynamics, fiscal considerations, and changes in the United States’ strategic priorities amid increasing competition between great powers. This policy has the potential to reduce the operational capacity of missions through staff reductions, logistical limitations, and increased pressure on the sustainability of the UN peacekeeping funding system. These findings show that a high reliance on a single major contributor creates structural vulnerabilities in the multilateral security architecture and underscores the importance of diversifying funding sources to maintain the effectiveness of UN peace operations.